Identification of test rig for a quarter car active suspension systems - Abdul Rashid, Zarina (2009)
System Identification approach can be used to estimate the models and parameters of the passive system of a test rig for a quarter car active suspension systems. The passive suspension system is consists of sprung mass, unsprung mass, damper and hydraulic actuator. Identification of the system is carried out based on the experimental work of the test rig. The input of the system is an input signal from the LVDT sensor that be controlled by valve and two output signals of the system are the output signals from accelerometers. One output signal is taken from the accelerometer that placed at the body of the car and another one is placed at the tire of the car. Input signal excitation and data acquisition process are controlled by using Simulink. In order to estimate and validate the model and parameters, the data are process using the System Identification Toolbox in Matlab. Since the system is modeled as a linear model, linear ARX model is utilized as a model structure. Model parameter estimation for the passive systems is performed using ARX430 and ARX420 methods respectively. Through the validation process, percentage of the best fit can be reached more than 90% and the smallest LF, PFC and AIC criterions also can be reached. Hence, the model parameters of the system are acceptable.